Capital structure and financing choices : an Australian study : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Business Studies in Finance at Massey University - Cross, Roy (Massey University, 2010)
This thesis uses a modified pecking order framework to analyse financing choices for Australian firms. The traditional pecking order model has been extended to allow a non-linear relationship between a firm’s requirements for external capital (the financial deficit) and the amount of external debt used to meet these requirements. The pecking order theory predicts that firms will follow a defined hierarchy of financing choices with internal funds being used first, followed by external debt and as a last resort the issuance of external equity. The sample used includes ASX listed industrial firms from 1995-2009 and includes a total of 702 unique firms and 3,852 individual firm year observations. My main finding is that Australian firms do not follow the pecking order as closely as in other markets as the model explains less of the variation in debt issuance. Importantly I find that this is not related to debt capacity constraints, which has been hypothesized by other authors as a legitimate reason why firms, small firms in particular, would not appear to be following the pecking order theory. I use Altman’s Z-Score, which is a commonly used measure of financial distress, to identify firms that are relatively unconstrained in terms of debt capacity. I find that while controlling for debt capacity does improve the explanatory power of the model, the improvement is only marginal. However I do find evidence against the static trade-off theory of capital structure. In particular firms that are unconstrained in terms of debt capacity and not facing significant capital expenditure do not increase leverage towards an optimal capital structure in the manner predicted by the static trade-off theory. In many cases they actually decrease leverage further. I hypothesize that at least part of the reason for these findings is due to taxation differences, with the imputation credit system in Australia effectively removing the tax advantage of debt for domestic investors. Another important factor that could explain the lower explanatory power of the pecking order model could be the more accepted use of warrants and rights issues to raise equity, which have been argued to have lower asymmetric information costs than issuing straight equity.
No declaration form provided. Digital copy may differ from hard copy.
Keywords: Corporate finance; Australia; Pecking order model; Financing choices